1989
DOI: 10.1016/0378-1097(89)90338-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of intestinal glycoproteins by Bacteroides vulgatus

Abstract: Bacteroides vulgatus, isolated from a patient with Crohn's disease, produced in gnotobiotic rats 7 constitutive enzymes that might be concerned with the degradation of intestinal glycoproteins. Furthermore Bacteroides vulgatus caused an almost complete loss of blood group antigenicity of the intestinal glycoproteins. Enzymes with the potency to release toxic compounds from hepatic conjugates and plant glycosides, beta-glucuronidase and beta-glucosidase, respectively, were only detectable in small amounts. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Similar results were previously observed using culture, PCR-cloning-sequencing, and FISH. 14,17,18 Interestingly, B. vulgatus degrades mucus 26 and initiates colitis in transgenic HLA-B27 rats. 27 Similarly, the Ruminococcus gnavus subgroup belonging to the C. coccoides group is known to degrade mucins.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were previously observed using culture, PCR-cloning-sequencing, and FISH. 14,17,18 Interestingly, B. vulgatus degrades mucus 26 and initiates colitis in transgenic HLA-B27 rats. 27 Similarly, the Ruminococcus gnavus subgroup belonging to the C. coccoides group is known to degrade mucins.…”
Section: Discussionmentioning
confidence: 97%
“…Bacteroides vulgatus isolated from IBD patients secrete mucin‐degrading enzymes. 52 However, lower levels of sulfate on Muc2 could also be beneficial, since fewer sulfates available for metabolism by sulfate‐reducing bacteria could result in less production of toxic sulfides. Increased numbers of sulfate‐reducing bacteria have been demonstrated in ulcerative colitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results therefore suggested that the Bacteroides species have an invasive effect on the host enteric tissue thereby causing a systemic antibody response even though they are considered to be commensal bacteria. Indeed, B. vulgatus has been reported to produce mucindegrading enzymes, which could profoundly affect the mucosal barrier function (20). Furthermore, the outer membrane antigens of B. vulgatus were found to be intimately associated with the enhancement of inflammation in a carrageenan-induced IBD model (4).…”
Section: Discussionmentioning
confidence: 99%